PENDEKATAN KONSELING SPIRITUAL PADA LANJUT USIA (LANSIA) - St. Rahmah (Al-Hiwar : Jurnal Ilmu dan Teknik Dakwah, 2015)
Later years and growing old is a natural process that is experienced by humans, slowly but surely going to happen and have a direct impact on the various aspects of life. Facts show various problems can occur because of unpreparedness of the elderly in accepting all the changes that happened. Supposedly the elderly should be able to complete the development tasks optimally and ultimately having personal integrity fully in receiving physical decline, and social well psikhis. The readiness of the elderly in receiving various reduction in the physical, psychological and social well can help achieve multidimensional health in living the rest of life in old age. Spiritual counseling approach with various techniques such as prayer, teaching the concepts of spiritual, scriptural references, spiritual experiences, spiritual confrontation, prayers shared between the client and the counselor, the urge to forgive, the use of community or religious groups, prayer client, religious bibliotherapy. Spiritual counseling approach is very appropriate for the elderly so that old age life more meaningful and they can fill their lives with things that are productive and useful.